Porównanie oceny obciążenia statycznego przedstawicieli handlowych różnych firm = Comparison evaluation of static load of sales representatives from different companies - Justyna Gierczak (Kazimierz Wielki University, 2016)
Gierczak Justyna. Porównanie oceny obciążenia statycznego przedstawicieli handlowych różnych firm = Comparison evaluation of static load of sales representatives from different companies. Journal of Education, Health and Sport. 2016;6(6):213-222. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55337 http://ojs.ukw.edu.pl/index.php/johs/article/view/3563   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Porównanie oceny obciążenia statycznego przedstawicieli handlowych różnych firm Comparison evaluation of static load of sales representatives from different companies   Justyna Gierczak   SKN Ochrony Środowiska, Sekcja Higieny pracy Uniwersytet Przyrodniczy w Lublinie   inż. Justyna Gierczak Opiekun prof. dr hab. Bożena Nowakowicz-Dębek SKN Ochrony Środowiska, Sekcja Higieny pracy Uniwersytet Przyrodniczy w Lublinie     Streszczenie   1. Wprowadzenie i cel pracy Jednym z czynników zaliczających się do zagrożeń w środowisku pracy jest obciążenie mięśniowo-szkieletowe. Stanowisko przedstawiciela handlowego jest stosunkowo nowym, dlatego warto bliżej zapoznać się z jego charakterystyką. Celem pracy było zbadanie i porównanie wielkości obciążenia statycznego w środowisku pracy przedstawicieli handlowych dwóch różnych firm. 2. Materiał i metoda Ocena obciążenia dotyczyła przedstawicieli handlowych pracujących w dwóch różnych firmach zróżnicowanych branżowo. Badanie zostało przeprowadzone w maju 2016 r. i została do niego wykorzystana metoda OWAS (Ovako Working Posture Analysis System). 3. Wyniki Przedstawiona ocena przedstawiciela zakładu 1. potwierdza, że w przypadku badanego stanowiska pracy istnieje średnie ryzyko wystąpienia nadmiernego obciążenia układu mięśniowo-szkieletowego. Świadczy to o tym, iż pozycje ciała przyjmowane przez pracowników, mogą mieć negatywne skutki zdrowotne, dlatego warto rozważyć propozycję zmiany warunków pracy. Przedstawiona ocena pracownika zakładu 2. wykazała, że w przypadku analizowanego stanowiska pracy istnieje małe ryzyko wystąpienia nadmiernego obciążenia układu mięśniowo-szkieletowego. Świadczy to, że pozycje ciała przyjmowane przez pracowników w przedstawionym wymiarze czasowym nie powinny mieć negatywnych skutków zdrowotnych, więc nie trzeba zmieniać warunków pracy. Wskazane jest aby okresowo przeprowadzać ocenę na obu stanowiskach pracy. 4. Wnioski Należy indywidualnie podchodzić do każdego stanowiska przy ocenie ryzyka obciążeniem statycznym. Gdy występuje średnie ryzyko przeciążenia układu mięśniowo-szkieletowego nie jest obowiązkowe natychmiastowe zmienianie warunków pracy tego stanowiska jednakże wskazana jest regularna jego ocena oraz rozważenie możliwości korzystnych zmian. Obciążenie statyczne jako rozpowszechniający się czynnik zagrożenia powinno być częściej brane pod uwagę i badane przez specjalistów związanych z dziedziną BHP.   Słowa kluczowe: obciążenie  w pracy, ryzyko zawodowe, zdrowie, bezpieczeństwo.   Abstract   Introduction and aim. One of the factors falling to the risks in the work environment is a load of musculoskeletal. The position of sales representative is relatively new, so it is worth a closer look at his characteristics. The aim of the study was to investigate the static load environments sales representatives of two different companies and compare them. Material and method. Rating load concerned two sales representatives in a variety of different companies of sector. The survey was conducted in May 2016. And was to him the method used OWAS (Ovako Working Posture Analysis System). Result. This assessment representative 1. confirms that in case of an investigational job medium, there is a risk of overloading the musculoskeletal system. This shows that the body positions taken by the employee may have a negative impact because it is worth considering a proposal to amend the conditions of work, but it is not necessary for immediate execution. This assessment Employee No. 2 showed that in the case of an investigational workplace there is a small risk of overloading the musculoskeletal system. This shows that the body positions taken by an employee in the present-time should not have any negative effects, so you do not need to change the working conditions. It is advisable to periodically carry out an assessment of the two positions. Conclusions. It should be approached individually for each position in the risk assessment static load. When there is a medium risk of overloading the musculoskeletal system is not mandatory immediately change the working conditions of this position, however, it is indicated for the regular evaluation and consider the possibility of positive changes. Static load as spreading risk factor should be taken more into account and examined by experts associated with the field of health and safety.   Keywords: workload, safety, health, risk.